Community Participation in the Village Owned Enterprise Program in Sidoarjo Regency - Nabila Azza Zhafira; Ilmi Usrotin Choiriyah (Indonesian Journal of Public Policy Review, 2022)
This study was to determine the involvement of community participation in the village-owned enterprise program in Sidokepung Village, Buduran District, Sidoarjo Regency. The research method uses descriptive qualitative. The results of the research can be said that community involvement is quite good, although only a few. In reality, not all community members in Sidokepung Village are involved, this is based on the lack of socialization from the BUMDes management to the community related to the BUMDes program, then busy work is also still a barrier, housewives who still do not want to be involved because they think that is there any reciprocity if they participate in BUMDes activities, and there are still those who question whether the BUMDes programs are long-term and able to provide benefits for them.